The use of endobronchial ultrasound guided transbronchial needle aspiration specimens for next generation sequencing in non-small cell lung cancer: a clinical perspective - Stoy, Sean; Murgu, Septimiu (Journal of Thoracic Disease, 2017)
The National Comprehensive Cancer Network (NCCN) 2017 Clinical Practice Guidelines for Non-Small Cell Lung Cancer (NSCLC) recommend utilization of a procedure that allows concurrent diagnosis, staging and procurement of material, which is sufficient for genetic testing (1).